Thin Film Gadolinium-Doped Ceria (GDC) Interdiffusion Layer Fabricated by a Novel Chemical Solution Deposition (CSD) Process for Solid Oxide Fuel Cells (SOFCs) - Oh, Eun-Ok; Whang, Chin-Myung; Hwang, Hae-Jin; Song, Eun-Hwa; Min, Kyoung-Yeol; Lee, Jong-Ho; Lee, Hae-Weon (AMER SCIENTIFIC PUBLISHERS, 2012)
A thin-film gadolinium-doped ceria (GDC) interdiffusion barrier layer was fabricated on a rigid half-cell substrate by multiple spin coating of chemical solution and low-temperature sintering of 1000 degrees C. Incorporation of GDC nanoparticles into the chemical solution resulted in a relatively dense and uniform microstructure without major microstructural heterogeneities. A highly active LaSrCoO3 (LSCF) cathode layer was also deposited by multiple spin coating of LSCF chemical solution containing LSCF nanoparticles, and was sintered at 950 degrees C to maintain thermodynamic stability of the GDC interdiffusion barrier layer with the help of the GDC-LSCF cathode functional layer. A cell developed on a conventionally process half cell exhibited excellent power outs of 810, 470, and 240 mW/cm(2) at 650, 600, and 550 degrees C, respectively.